EDUKASI DENGAN METODE SCHOOL WATCHING MENINGKATKAN KESIAPSIAGAAN SISWA DALAM MENGHADAPI BENCANA - Putu Susy Natha Astini (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2018)
The purpose of this reasearch is to find out some effects in educational with School Watching method about student preparedness in facing disaster. The kind of reasearch is Pre-Experimental Design with One-Group Pretest-Posttest design. The sampling tehnich use proportionate stratified random sampling, with the number of samples are 70 persons. The result of there search shows that the preparedness of the students before being given the education was the almost-ready category which consisted 30 people (42,9%) and after being given the education, the result of the research indicates that there was such an improvement in students preparedness with the result, most the students are in the very-ready category that consists 36 people (51.4%). The result of the research was tested by statistical test of wilcoxon, got value of ρ-value = 0.0001 alpha (0,05), it is concluded that there is a significant influence of education with School Watching method toward student preparedness in facing disaster at SDN 16 Kesiman Denpasar. Based on the results of the study, it is suggested that need to improve the provision of disaster materials by developing interesting methods to prepare all students for disaster.